Cultish : the language of fanaticism - Montell, Amanda (Harper Wave, an imprint of HarperCollinsPublishers, 2021)
"From SoulCycle to Scientology, we're all obsessed with cults. Linguist Amanda Montell examines the language cults use to draw us in"--